Umar Bin Abdul Aziz's Role through Zakat to Improve Islamic Public Financial - Iqbal, Ahmad; Harahap, Soritua Ahmad Ramdani; Rizqon, Abdul Latif (Penerbit Goodwood, 2025)
Purpose: Good zakat management has always been a challenge for zakat institutions. For this reason, the main reference that is often used is to imitate the management of zakat that has been done by Umar bin Abdul Aziz. This study aims to determine the role of public financial management through the zakat instrument applied during the reign of Umar bin Abdul Aziz. Islamic public financial management, especially zakat, aims to achieve the goal of community life, namely prosperity and welfare. Methodology/approach: This research method is a literature-based qualitative research to explore the role of zakat management as Islamic public policy during the time of Umar bin Abdul Aziz. This research takes various references related to the role of Islamic public policy in a structured manner ranging from primary and secondary books and journals that discuss this matter. Results/findings: The conclusion of this research shows that the key to success during the reign of Umar bin Abdul Aziz was the fair and targeted management of zakat. The success carried out by Umar bin Abdul Aziz was by conducting several programs, including integrating the management of zakat by the state, being selective in choosing amil, expanding the object of zakat, and distributing the distribution of zakat funds on target. By doing this, Umar bin Abdul Aziz was able to provide a general picture of being able to manage Islamic public finances so that all levels of society benefited. Conclusion: Zakat is one of the pillars of Islam that must be practiced. Zakat also plays a role in eliminating the gap between the poor and the rich. In addition, zakat also plays a role in reducing the poverty rate in a country. Limitations: In this study, researchers focus on the strategy and management of zakat during the reign of Umar bin Abdul Aziz in managing Islamic public finance to create justice for the entire community. Contribution: This research has a contribution to explain how the management of zakat instruments should be fair and right on target. The potential of zakat is very high but the achievement of zakat fund collection has not been able to be absorbed properly so that the distribution of zakat has not been evenly distributed.